Analysis of students mathematical communication skills using Bruner’s theory - AF Rachman; H Bharata; A Asmiati (Pascasarjana Universitas Pendidikan Indonesia, 2020)
Mathematical communication skills have an important role in mathematics because it can help students to express their understanding. This study aims to analyze the students mathematical communication skills using Bruner’s theory in the system of three-variable linear equations material. The type of research is a qualitative descriptive research. The research was conducted at SMAN 4 Kotabumi with the subjects in this study are 129 students of X grade. The data collection technique used was a written test of mathematical communication skills. The results of this study indicate that students’ mathematical communication skills are still relatively low. Constraints found by researchers that led to students’ low mathematical communication skills are: (1) students have not been able to understand the problem and explanation correctly; (2) students have not been able to do the calculations correctly when associating with system variables equations; (3) students cannot conclude the results correctly.